Polycystins and primary cilia: primers for cell cycle progression - Zhou, Jing (Annual review of physiology, 2009)
Polycystins are a family of eight-transmembrane proteins united by sequence homology. The name stems from the identification of mutations in genes encoding polycystin-1 and -2 in polycystic kidney diseases. This review discusses recent topics in polycystin research, with a focus on the role of polycystin-1 and polycystin-2 in primary cilia and the cell cycle. Polycystins appear to play key roles during development, but a major question is their function in mature organs. Their roles in primary cilia, shear stress sensation, alteration of intracellular calcium, and planar cell polarity are examined. The third-hit hypothesis of polycystic kidney disease is discussed.